METHODICAL PRINCIPLES OF APPLYING DIGITAL TECHNOLOGIES IN THE TRAINING OF FUTURE SKILLED WORKERS (Innovative professional education, 2023)
The use of digital technologies in the future skilled workers training is determined by their prevalence and availability in the industry market. The training organization effectiveness of using digital technologies depends on the proficiency level in these technologies of both teachers and students. It is established that teachers of vocational (vocational-technical) education system should take into account the impact of the digital technologies use on their beliefs and strategy of organizing the educational process.
Keywords: digital technologies, specific principles, vocational education, methodical principles, training of skilled workers